KONTROVERSI HALAL-HARAM ASURANSI SYARIAH - Dodih Suhardih (IAIN Ambon, 2018)
Insurance is still debated among scientists when viewed in terms of Islamic law. Contemporary Islamic jurists are fully aware that the legal status of insurance has not been determined by previous Islamic law experts (experts). The application of Takāful is now the result of the struggle between understanding Islamic law and the reality that occurs. These problems need to be reviewed in the order of Islamic law in depth. This paper aims to offer Shariah aspects in the application of Takāful (Sharia Insurance), Takāful insurance law (Sharia Insurance), scholars' views on Takaful (Sharia Insurance), compare the characteristics of Takāful (Sharia Insurance) and Conventional Insurance, as well as the author's analysis of Halal insurance for Islamic insurance.